Potential probiotic goat yogurt – a review (Research, Society and Development, 2023)
Functional foods have been gaining prominence in recent years due to the greater search for healthy eating. The effects responsible for its benefits are metabolic and physiological, capable of providing better performance to the body by its regular consumption, like yogurt, a fermented milk so popular among all audiences. Due to the scarcity of published references regarding goat dairy products, the bibliographic study of the characteristics of goat yogurt with probiotic potential is considered of great importance in order to investigate the functionality and satisfactory results in addition to the organoleptic characteristics, but mainly in the sensorial and technologies. In this context, goat yogurt, as explained in the study and corroborated in bibliographical research, constitutes a food of high nutritional and functional value, presenting a higher acceptability index given the improvements in sensory attributes, in terms of flavor, aroma and texture, given the potential emphasized in the literature when added ingredients such as probiotics, prebiotics, pulps, extracts and among others, becoming a product with better organoleptic and bioactive functional properties.